A study of the phonetic changes of Arabic loanwords in Balochi: بررسی تغییرات آوایی وام واژه های عربی در زبان بلوچی (Journal of the College of Languages (JCL), 2024)
Abstract  Lanɡauaɡes, like humans, need communication and interaction to prosper. One of the ways for a language to flourish is to borrow words from other languages. The southern regions of Iran and the coastal countries of Persian Gulf have had strong cultural relations since old times, with language being a dimension of these relations. With their land being geographically located in the realm of Islamic civilization and being Muslims,  Baloch people have had strong connections with the Arab world and the Arabic language.Thus, many Arabic words have made their ways into Balochi language either directly or indirectly through persian language. Since each language has its own unique sound structure, these loanwords have undergone phonetic changes after entering the Balochi. This article is an attempt to study the phonetic changes of Arabic loanwords in Balochi in a descriptive-analytical manner. This study has  a "diachronic" and ”historical” approach. The phonetic changes of different types can be found in these loanwords, among them “substitution”, “metathesis”, “elision”, and “epenthesis”. The focus of this study is mainly on ”substitution”. The results indicate that the loanwords in Balochi language, especially those with “substitution” in them, have more diversity compared to Arabic loanwords in Persian. This article will showcase unique types of “substitution” in Arabic loanwords found in Balochi language.چکیده زبان به مانند انسان برای ارتقا و غنای خود به ارتباط و تعامل نیاز دارد، چنان که یکی از راههای بالندگی و غنای یک زبان، وامگیری از دیگر زبانها است. مناطق جنوبی ایران با کشورهای ساحلی جنوب خلیج فارس، از دیرباز روابط فرهنگی پررنگی داشته‌اند که از جمله ابعاد این مناسبات، حوزه زبان است. در این بین زبان بلوچی به حکم موقعیت جغرافیایی زیست بومِ گویشورانش در عرصه تمدن اسلامی محصور بوده و از آن روی که بلوچها مسلمان بوده‌اند ناگزیر مناسباتی تنگاتنگ با زبان عربی داشته‌اند .بدین ترتیب واژگان فراوانی با واسطه زبان فارسی و یا بدون واسطه مستقیما از زبان عربی به زبان بلوچی انتقال یافته‌اند. از آنجا که هر زبانی ساختار آوایی ویژه خود را دارد این وامواژه‌ها پس از ورود به زبان بلوچی دچار دگرگونی آوایی شده‌اند.این مقاله به عنوان مطالعه‌ای «درزمانی» و «تاریخمند» در صدد است که با روش توصیفی-تحلیلی دگرگونیهای آوایی موجود در این وام واژهها را یافته و مورد واکاوی قرار دهد.دگرگونی‌های آوایی عبارتند  از «ابدال»، «قلب»، «حذف» و « درج» که  در این مقاله «ابدال» به صورت اختصاصی مورد مطالعه قرار گرفته است.نتایج نشان‌دهنده آن است که «ابدال» وام‌واژه‌ها در زبان بلوچی به نسبت وام‌واژه‌های عربی موجود در زبان فارسی از تنوع بیشتری برخوردار است که شفاهی بودن فرهنگ و ادبیات بلوچی در این امر بسیار  تأثیر داشته است.واژگان کلیدی: زبانشناسی، دگرگونیهای آوایی، وام‌واژه، زبان عربی، زبان بلوچیReceived on 11/7/2023 Accepted on 20/8/2023 Published on 2/1/2024